Fast End-to-End Simulation and Exploration of Many-RISCV-Core Baseband Transceivers for Software-Defined Radio-Access Networks - Bertuletti, Marco; Zhang, Yichao; Abdollahpour, Mahdi; Riedel, Samuel; Vanelli-Coralli, Alessandro; Benini, Luca (2025 62nd ACM/IEEE Design Automation Conference (DAC), 2025)
The fast-rising demand for wireless bandwidth [1] requires rapid evolution of high-performance baseband processing infrastructure. Programmable many-core processors for software-defined radio (SDR) have emerged as high-performance baseband processing engines, offering the flexibility required to capture evolving wireless standards and technologies [2]-[4]. This trend must be supported by a design framework enabling functional validation and end-to-end performance analysis of SDR hardware within realistic radio environment models. We propose a static binary translation based simulator augmented with a fast, approximate timing model of the hardware and coupled to wireless channel models to simulate the most performancecritical physical layer functions implemented in software on a many (1024) RISC-V cores cluster customized for SDR. Our framework simulates the detection of a 5 G OFDM-symbol on a server-class processor in 9.5 ~s-3 ~min, on a single thread, depending on the input MIMO size (three orders of magnitude faster than RTL simulation). The simulation is easily parallelized to 128 threads with 73-121 × speedup compared to a single thread.